The Effectiveness of Interpersonal Communication of Faith-Based Organizational Media Team in Producing Dakwah Content - HRP, Sri Maharani; Fauziah, Kholifatul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This study aims to explain the effectiveness of the faith-based media team's interpersonal communication as a team that produces da'wah content in Indonesia. At first, the spread of Islamic teachings in Indonesia developed only in mosques, but over time, da'wah has evolved into digital da'wah (da'wah through online media). anything that can be used to spread da'wah content. Because of this, the Muhammadiyah Central Leadership digital tabligh studio team, as the team that produces da'wah content, is deemed necessary to attach the effectiveness of interpersonal communication to facilitate the process of producing da'wah content. This organization is a non-profit organization engaged in charity and business that generally relies on volunteers to develop the organization. Theoretically, this research has implications for the effectiveness of interpersonal communication in related organizations in creating da'wah content. This study uses a descriptive qualitative approach. The use of this method is considered to be able to describe in detail the problems studied. Furthermore, this study will explain how the effectiveness of interpersonal communication of the digital tabligh studio team in producing da'wah content. Then, this study will identify what factors, both internally and externally, can influence the effectiveness of interpersonal communication of the digital tabligh studio team in creating da'wah content.